INVENTARISASI POTENSI EKOWISATA DI JALUR BUKIT TEPANGGANG HUTAN ADAT GUGUK KABUPATEN MERANGIN - Albayudi, Albayudi; Adriadi, Ade; Irgi Firaa, Mohd; Saputra , Rizky; Kurnia, Agung (Naturalis: Jurnal Penelitian Pengelolaan Sumberdaya Alam dan Lingkungan, 2025)
The Guguk Customary Forest has a forest area of 690 ha. Since 2003 it has been designated as a customary forest area through Merangin Regent Decree Number: 287 of 2003, precisely on November 23 2003. Potential attraction object Natural tourism (ODTWA) in the Guguk Traditional Forest area consists of several objects, namely potential natural views at the top of Tepanggang Hill, hiking/tracking in the Guguk traditional forest area, fishing, swimming and exploring the area using boats or bamboo rafts along the Betung River. and enjoy the Betung River waterfall., Potential flora in the form of various types of rare trees, which based on the results of the KKI-Warsi survey there are 10 families with a total of 167 trunks with an average diameter of more than 90cm and Dipterocarpaceae as the dominant tree group, orchards owned by residents and the damang tree where bees place their hives and produce honey. Potential fauna diversity, based on the results of a survey of vertebrate animals by Fauna Flora Indonesia in the Batang Nilo-Nilo Cold production forest area, which was recorded as consisting of 83 types of mammals, 91 types of Herpetofauna, and 221 types of Aves. The aim of this research is to inventory the flora and fauna on the Tepanggang hill climbing route in the Guguk traditional forest in Guguk Village, Merangin Regency, Jambi Province. The Guguk Traditional Forest has one route that has been inventoried, namely the Bukit Tepanggang route which has the potential for birds, mammals, primates and plants. The potential flora and fauna found on the route are 9 types of birds, 3 types of primates, 2 types of mammals, 20 types of plants, rivers and 2 viewpoints. The planning for observation activities on the tepanggang hill route of the Guguk Traditional Forest includes activities to recognize mammals, observe primate activities, identify tree types in the area, birdwatching, rivers and viewing peaks